IT MEANS INCLUSION A CREATIVE APPROACH TO DISABILITY AND TELECOMMUNICATIONS POLICY IN AUSTRALIA - Ellis, Katie (Swinburne University of Technology, 2012)
Christopher Newell was both optimistic and sceptical regarding the potential of digital technologies and advanced telecommunications to assist individuals with disability (Newell 1998, Goggin & Newell 2000, Goggin & Newell 2003). With Newell's body of work in mind, this paper considers current policy issues which intersect disability, telecommunications and participation that have garnered government and public attention in Australia in recent years. Three important case studies are offered - the national broadband network, digital television and mobile telephones. I demonstrate the tangible benefits innovative use of these telecommunications technologies can deliver, in assisting individuals with disabilities, while cautioning their potentially disabling elements. Using an ethos of 'accessibility 2.0' (Ellis & Kent 2011), the paper takes the policy discussion beyond the provision of infrastructure to consider issues of accessibility and usability, relevant to disabled users and, by extension, us all (Goggin 2008b). This paper recommends a reformulation of telecommunications policy to recognise different accessibility requirements are needed for different impairments and that these may benefit the mainstream community which is interested in customising its digital technologies (Jaeger 2006). An extraordinary value lies in using telecommunications - such as the NBN, digital television and mobile telephones - to connect people with disability who are physically and socially marginalised.